PEMBERIAN TEKNIK DISTRAKSI MENGGAMBAR DAN MEWARNAI UNTUK MENURUNKAN ANSIETAS SELAMA HOSPITALISASI PADA ANAK DBD DI RUMAH SAKIT - Jawiah Jawiah; Rehana Rehana; Umar Hasan Martadinata; Yeny Elviani; Jenny Amelia (Journal of Complementary in Health, 2022)
Background: Children with Dengue Hemorrhagic Fever must immediately receive treatment with hospitalization (hospitalization), the most common main response when children undergo hospitalization is anxiety (anxiety). Children's anxiety levels can be overcome by offering therapies that are able to create a sense of security and comfort for children, one of which is by presenting drawing and expressing distraction techniques. Drawing and aims aim to make children happy, feel not afraid and can be used as one of the entertainments when children are hospitalized. Methods: This case study design is a descriptive design in the form of a case study with a process approach consisting of assessment, diagnosis, planning (intervention), implementation (implementation), evaluation and documentation. The subject of the case study again was two DHF pediatric patients who experienced the same problem, namely anxiety. This case study was conducted at Siti Fatimah Hospital Palembang in 2022. The data collection technique was by means of observation, interviews and filling out case study instruments for 3 days in the treatment room. Result : The implementation given is in the form of drawing distraction technique and it worsens the anxiety experienced by pediatric patients during hospitalization. Scores decreased significantly after the drawing and storytelling techniques were applied. Conclusion: The drawing distraction technique can reduce anxiety in children who experience hospitalization, the anxiety score after the drawing distraction technique decreases.